The Effect of Philosophy for Children (P4C) Curriculum on Formulating Question Skills of Children with Special Learning Disabilities - Filiz Karadağ (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
The philosophy for children approach is a method of developing critical thinking in children through philosophical dialogue. Questioning skills, which are an important stage of critical thinking, is an intellectual process that takes place in order to make an experience meaningful. Asking questions is one of the oldest learning-teaching tools used in the inquiry process. Children with special learning disabilities (SLD) have various distinctive features in terms of cognitive and social development. The development of high-level thinking skills, which includes a whole set of cognitive skills such as thinking, knowing, perceiving, reasoning, making decisions, following a thought, remembering, summarizing, generalizing, predicting, and inferring, is not yet sufficiently developed in young children with special learning disabilities. Simon (1979) suggested that using the “Philosophy with Children” approach would be effective in improving the cognitive and social skills of children with SLD. Accordingly, in this study, it was investigated effectiveness of Philosophy for Children curriculum on the question-formulating skills of children with SLD. In the research, one group pre-test post-test random experimental design, which is one of the quasi-experimental designs, was used. The applications were implemented for one hour, once a week for ten weeks. The study group consists of 13 children who are in the 2nd and 3rd grade and diagnosed with SLD. The data were collected with the "interview form containing the philosophical inquiry text and questions" and the audio recordings of the training sessions. The inductive data analysis method was used in the analysis of the obtained data. The findings indicated that, the "Philosophy with Children" curriculum improved the level of questions that children with SLD create in their philosophical inquiry processes.